Diskursus Estetika Realisme Sosialis: Kajian Filsafat Pendidikan Moral atas Sastrawan Kreatif di Bandung - Robby Habiba Abror (UIN Sunan Kalijaga Yogyakarta, 2018)
Culture and art attached to the city of Bandung. The dialectical process in the realm of aesthetics becomes an integral part of the discourse of literaryists and literary connoisseurs in the flower city. Although it is debatable whether Bandung poets purely ideological socialist, realist, or religious maybe even a combination of socialist socialist or socialist realism, did not reduce the passion of creativity of creative writers in Bandung to give birth to various forms of literary artwork needed by its citizens to build a city with a moral breath and heed the elements of nature in harmonizing modernity and local culture. The digital age makes the media a locus of creative literary education and praxis to build the aesthetic of socialist realism based on morality.[Kebudayaan dan kesenian melekat pada Kota Bandung. Proses dialektik dalam ranah estetika menjadi bagian integral dalam diskursus para sastrawan dan penikmat sastra di kota kembang itu. Kendati masih diperdebatkan apakah para sastrawan Bandung murni berideologikan sosialis, realis, ataukah religius bahkan mungkin juga kombinasi realisme sosialis atau sosialis religius, tak mengurangi gairah kreativitas para sastrawan kreatif di Bandung untuk melahirkan berbagai bentuk karya seni sastra yang dibutuhkan warganya untuk membangun kota dengan nafas moral dan mengindahkan unsur alam dalam mengharmoniskan modernitas dan budaya lokal. Era digital menjadikan media sebagai lokus pendidikan sastra kreatif dan praksis untuk membangun estetika realisme sosialis berdasarkan moralitas.]